RANCANG BANGUN SISTEM INFORMASI GUIDELINE SYSTEM MULTI-TENANT BERBASIS WEB MENGGUNAKAN METODE SYSTEM DEVELOPMENT LIFE CYCLE (SDLC) PADA WIT ID - Muhamad Al-Fazri, Rendy; Nugraha, Yopi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of the software development industry demands higher structural standards for managing technical documentation and developer manual books. However, many technology companies face operational constraints due to uncentralized and fragmented document storage. This study aims to design a web-based multi-tenant Guideline System as a centralized SaaS platform using the SDLC method. This platform operates as a knowledge base ecosystem where external enterprises can establish organization profiles, manage internal workspace instructions, and share handbooks seamlessly like a tech-focused social network. Built upon the Laravel framework, the platform leverages the MVC architecture to ensure secure data isolation between tenants. This research at WIT ID delivers a verified architectural blueprint designed to eliminate documentation redundancy and optimize the efficiency of digital knowledge sharing environments